Fish and fisheries of tropical estuaries - Blaber, Stephen J. M. (Chapman & Hall, 1997)
Tropical estuaries are among the most modified and threatened of aquatic environments, supporting innumerable fisheries essential to the regions in which they occur. This book synthesizes the wealth of data available in this area, much of it being brought together by Stephen Blaber for the first time. It will provide readers with a comprehensive understanding of the fishes, the environments in which they live, and the management of biologically healthy estuaries and sustainable fisheries.